Constructivism strategies and their effect on accomplishment of Arabic grammar rules curriculum for fifth-grade primary students, including the (placemat) strategy as a Framework model - Al-Zerkani, Abdul-Zahra Kezar Jaadir; Al-Sa'adi, Saad Sawadi Ta'ban (Al-Adab Journal, 2020)
The aim of research is to identify modern strategies in the acquisition of Arabic language among fifth-grade primary school students, including the (placemat) strategy as a model.” To achieve this, the researcher followed the experimental approach adopted on experimental design distinguishing by partial control feature, which is the design of the experimental group, and the control group with the post test. The researcher intentionally chose his research sample consisting of (64) students, divided into two groups. By using consistent manner in both of the student groups, the researcher took into account a number of variables, namely: (the time age calculated by the months and the academic achievement of the parents and the previous year grades in language subject Arabic), from the academic year 2019-2020